Synthesis of lead selenide (PbSe) quantum dots for photovoltaic applications - Yang, Shuai (2010)
Lead Selenide (PbSe) quantum dots were synthesized by a room – temperature microemulsion route. By varying the water to surfactant ratio, the particle size of the synthesized PbSe quantum dots could be adjusted while Energy Dispersive X-ray Spectroscopy (EDX) analysis showed the elemental composition of Pb and Se remained at close to 1 : 1. PbSeO3 phase was present in X-ray Diffraction (XRD) patterns that suggested the PbSe had low stability due to lack of capping agent. Transmission Electron Microscopy (TEM) results confirmed that the particle size increased with increasing water to surfactant ratio, and UV-vis NIR Absorption Spectra of the PbSe quantum dots showed a red shift also with increasing water to surfactant ratio, the corresponding band gap was more than 1eV, which was larger than that of bulk PbSe.